Advanced numerical insights for an effective seismic assessment of historical masonry aggregates. (15th June 2023) - Schiavoni, Mattia; Giordano, Ersilia; Roscini, Francesca; Clementi, Francesco
Highlights: The aggregates' connections significantly affect the structural response. An old structure is analyzed with continuous and discontinuous numerical models. Evaluation of the response under repeated accelerograms (seismic sequence) Indications are given of the most appropriate approach for old structures' analysis. Abstract: The structural assessment of ancient masonry structures is still a challenging task. The main reasons have been related to the shortage of information in the materials' characterization along with the complex geometry and different evolutions of its constituents' parts through the time. Scientific studies on the evaluation of the structural capacity and design of these masonry buildings have reported several modelling techniques. The goal of this work is to investigate the effectiveness of different numerical approaches in the simulation of the cyclic behaviour of historic masonry buildings under seismic loads. In addition, the damage level of the structural interconnections will be evaluated and what extent they affect the global instability. The specific case study seeks to examine an ancient palace with its civic tower hit by the 2016 Central Italy earthquake. A couple of masonry modelling are used: the first one is discontinuous (DM) and the second one is continuous (CM). Two models were set: one model replicated the structure as a whole, the other one considered only the tower. The DMs were studied with 3DEC© and LMGC90© software, where, in turn, different contact conditions were implemented. In parallel, the CMs were analysed with the Midas FEA NX©. The present research offers significant outcomes obtained from the non-linear dynamic analyses performed using the proper sequence recorded in that seismic event. Likewise, this document underlines the importance of the correct modelling techniques definition, based on the state of the case study, especially when an isolated tower is considered.